COAST (Cisplatin ototoxicity attenuated by aspirin trial): A phase II double-blind, randomised controlled trial to establish if aspirin reduces cisplatin induced hearing-loss. (December 2017) - Crabb, Simon J.; Martin, Karen; Abab, Julia; Ratcliffe, Ian; Thornton, Roger; Lineton, Ben; Ellis, Mary; Moody, Ronald; Stanton, Louise; Galanopoulou, Angeliki; Maishman, Tom; Geldart, Thomas; et al.
Abstract: Background: Cisplatin is one of the most ototoxic chemotherapy drugs, resulting in a permanent and irreversible hearing loss in up to 50% of patients. Cisplatin and gentamicin are thought to damage hearing through a common mechanism, involving reactive oxygen species in the inner ear. Aspirin has been shown to minimise gentamicin-induced ototoxicity. We, therefore, tested the hypothesis that aspirin could also reduce ototoxicity from cisplatin-based chemotherapy. Methods: A total of 94 patients receiving cisplatin-based chemotherapy for multiple cancer types were recruited into a phase II, double-blind, placebo-controlled trial and randomised in a ratio of 1:1 to receive aspirin 975 mg tid and omeprazole 20 mg od, or matched placebos from the day before, to 2 days after, their cisplatin dose(s), for each treatment cycle. Patients underwent pure tone audiometry before and at 7 and 90 days after their final cisplatin dose. The primary end-point was combined hearing loss (cHL), the summed hearing loss at 6 kHz and 8 kHz, in both ears. Results: Although aspirin was well tolerated, it did not protect hearing in patients receiving cisplatin (p-value = 0.233, 20% one-sided level of significance). In the aspirin arm, patients demonstrated mean cHL of 49 dB (standard deviation [SD] 61.41) following cisplatin compared with placebo patients who demonstrated mean cHL of 36 dB (SD 50.85). Women had greater average hearing loss than men, and patients treated for head and neck malignancy experienced the greatest cHL. Conclusions: Aspirin did not protect from cisplatin-related ototoxicity. Cisplatin and gentamicin may therefore have distinct ototoxic mechanisms, or cisplatin-induced ototoxicity may be refractory to the aspirin regimen used here. Highlights: Aspirin was well tolerated. Aspirin did not protect hearing at the doses and in the schedule investigated here. Cisplatin and gentamicin may have distinct ototoxic mechanisms. Qualitative data suggest protective aspirin effect but low power for hypothesis. Cisplatin-induced ototoxicity results in significant morbidity.